Examining mechanisms for gender differences in admission to intensive care units. (10th November 2019) - Hill, Andrea; Ramsey, Clare; Dodek, Peter; Kozek, Jean; Fransoo, Randy; Fowler, Robert; Doupe, Malcolm; Wong, Hubert; Scales, Damon; Garland, Allan
Abstract: Objective: To evaluate whether the male predominance of older people admitted to intensive care units (ICUs) is due to gender differences in the presence of spouses, partners, or children; rates of gender‐specific disease; or triage decisions made by health system personnel. Data Sources and Collection: Three population‐based datasets, 2004‐2012, of Canadians ≥65 years: provincial health care data from Manitoba (n = 250 190) and national data of nursing home residents (n = 133 982) and community‐based homecare recipients (n = 210 090). Study Design: Retrospective observational study, using multivariable Cox proportional hazards and logistic regression. Principal Findings: Males predominated in ICU admissions: from Manitoba (hazard ratio [HR] = 1.87, 95% CI = 1.80‐1.95), nursing homes (HR = 1.47, 1.35‐1.60), and homecare (odds ratio = 1.14, 1.11‐1.17). Adjustment for spouses, partners, and children did not attenuate this effect. The HR for gender was lower by 13.5 percent, relative, after excluding ICU care for cardiac causes. Male predominance was not present during a second ICU admission among survivors of a first ICU‐containing hospitalization (HR = 1.07, 0.96‐1.20). Conclusions: In three older cohorts, the male predominance of ICU admission was not explained by gender differences in the presence of a spouse, partner, or children, or cardiac disease rates. The third finding suggests that triage bias is unlikely to be responsible for the male predominance.